2020
DOI: 10.3390/antibiotics9100664
|View full text |Cite
|
Sign up to set email alerts
|

Anthelminthic Activity of Assassin Bug Venom against the Blood Fluke Schistosoma mansoni

Abstract: Helminths such as the blood fluke Schistosoma mansoni represent a major global health challenge due to limited availability of drugs. Most anthelminthic drug candidates are derived from plants, whereas insect-derived compounds have received little attention. This includes venom from assassin bugs, which contains numerous bioactive compounds. Here, we investigated whether venom from the European predatory assassin bug Rhynocoris iracundus has antischistosomal activity. Venom concentrations of 10–50 µg/mL inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…They observed that it had remarkable pleiotropic effects on the physiological, cellular, and molecular processes in adult male and female Schistosoma mansoni. Tonk et al (2020) investigated the antischistosomal activity of the venom from the European predatory assassin bug, Rhynocoris iracundus. The components of wasp venom are commonly categorized as (i) bioactive molecules such as serotonin, histamine, catecholamines, tyramine, acetylcholine, avonoids, and biologically active amines, (ii) high molecular weight proteins such as hyaluronidases, phospholipases, and antigen 5, and (iii) low molecular weight peptides such as mastoparan (Nakajima 1986).…”
Section: Discussionmentioning
confidence: 99%
“…They observed that it had remarkable pleiotropic effects on the physiological, cellular, and molecular processes in adult male and female Schistosoma mansoni. Tonk et al (2020) investigated the antischistosomal activity of the venom from the European predatory assassin bug, Rhynocoris iracundus. The components of wasp venom are commonly categorized as (i) bioactive molecules such as serotonin, histamine, catecholamines, tyramine, acetylcholine, avonoids, and biologically active amines, (ii) high molecular weight proteins such as hyaluronidases, phospholipases, and antigen 5, and (iii) low molecular weight peptides such as mastoparan (Nakajima 1986).…”
Section: Discussionmentioning
confidence: 99%
“…We used the recently established method to stimulate R. iracundus nymphs to display a defense posture and subsequently collected the venom as illustrated in Figure 2 [30]. This procedure performed with one individual assassin bug refers to one venom harvesting event.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study we already discovered that R. iracundus venom causes onlỹ 6% of hemolysis on porcine erythrocytes [30] and erythrocytes from different vertebrate species show different levels of hemolysis [57]. This suggests that assassin bug venom has selectivity on different erythrocyte types making assassin bug venom interesting for leukemia studies.…”
Section: Versatility Of Assassin Bug Venom Towards Defense Purposesmentioning
confidence: 99%
“…Wenngleich Venomics noch eine sehr junge Disziplin darstellt, konnten hier in der jüngeren Vergangenheit große Fortschritte erzielt werden. Während noch bis vor kurzem so gut wie nichts über die kleineren Gifttiere bekannt war, so wachsen unsere Kenntnisse über die Gifte von Raub fliegen, Raubwanzen, Wespen, Würmern und kleinen Spin nen wie der Wespenspinne stetig [20][21][22][23][24]. Aktuell laufende Forschungen zu den Giften von Bienen, Ameisen, weiteren Spinnen und einigen Fischen werden in Kürze abgeschlos sen sein.…”
Section: Das Junge Forschungsfeld "Venomics"unclassified